Pengaruh Debt to Equity Ratio dan Firmsize, Terhadap Return on Assets Pada Perusahaan Makanan dan Minuman - Fatma Lungga Hapsari; Farah Raissathana Arfatalitha (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study aimed to determine Debt to Equity Ratio (DER) and Firm Size on Return on Assets (ROA) on food and drink companies listed on the Indonesia stock exchange 2019-2023. This research method used multiple linear regression analysis with data processing using the tools STATA 17 program. The sampling method of this research used a porpusive sampling techniquw. The F-test results showed that simultaneously Debt to Equity Ratio (DER) and Firm Size had a significant effect on Return on Assets (ROA). The T-test result showed that partially, Debt to Equity Ratio (DER) and Firm Size had an effect Return on Assets (ROA). (Roosmawarni & Mauliddah, 2024)